Structural modeling of entrepreneur's effectiveness - Sorooshian, Shahryar; Zulkifli, Norzima; Yusoff, I.; Mohd Yusuff, Rosnah (IDOSI Publications, 2010)
One of the major economic issues in Middle-East countries is non-oil exports and its increased share in Middle-East economic development plans. Among these of great priority are pistachio production and its processing industry. This study identifies the significant factors in increasing success of Middle-East small and medium industries (SMI) especially pistachio industry, base on their entrepreneurs' characteristics (ECh). The prepared empirical structural equation model(SEM)based on three concepts of ECh, strategy making and performance of small and medium pistachio industry (SMPI), shows that there is a strong relation between ECh and performance of SMPI. The model considers both direct an indirect effects of each 27 defined variable of our concepts.